(untitled) (Educational Dimension, 2021)
In an environment of education reformation aimed at transition of higher education to competence based and individual approaches, we face the need to construct individual learning path for every future maritime professional. In this respect technology of adaptive learning based on modern ICT becomes of high importance. At the same time COVID-19 pandemic has changed system of education at all its levels, but the issue of quality and efficiency is still to be considered and studied by scientists and practitioners. Under these conditions the issue of adaptive information environment creation becomes relevant for training modern and competitive specialists. This environment should be based on implementation of adaptive technologies for education and training of maritime students, therefore, article provides investigation of pedagogical problem of future navigators’ professional culture building in training system of adaptive information environment of maritime educational establishment. Feasibility of adaptive learning technologies implementation is grounded as a tool for future navigators’ professional culture building in the process of their fundamental education and training. Example of higher mathematics adaptive learning implementation for future navigators at Kherson State Maritime Academy is considered. Higher mathematics adaptive learning was introduced through: adaptive feeding of educational content of the course; problems solving support based on examples and pre-created typical algorythms; adaptive testing; analysis of test tasks answers; system teacher support; constant support conditions for individual tasks completion; adaptive course navigation, etc. As the result of experiment there was found out that higher mathematics adaptive learning for future navigators presupposes: individual learning path designing; possibility to timely provide advising and objective control as well as evaluation; enhancement of learning activity and motivation of through improved degree of autonomy; promotion of students’ research skills development; creation of cooperation, partnership and maritime brotherhood atmosphere.